Implementation of a method using tritiated substrates as a diagnostic tool for OCTN2 deficiency. (Colombia Medica, 2008)
Introduction: The transport of carnitine into the cell is mediated by a high-affinity sodium-dependent plasmalemmal carnitine transporter, OCTN2. Carnitine is a zwitterion essential for the mitochondrial oxidation of long-chain fatty acids. Primary carnitine deficiency is a consequence of the deficiency of OCTN2. Objective: The objective of the present study was to analyse the oxidation rate of tritiated substrates by fibroblasts from patients suffering OCTN2 deficiency and controls. Materials and methods: Fibroblasts from patients and controls were incubated with [3H]-palmitate and [3H]-miristate and the oxidation of these substrates were measured in nmol/hour/mg protein. Results: We found depressed the oxidation of tritiated substrates in fibroblasts from patients suffering the deficiency of OCTN2 in more than 60%. Conclusion: This modified technique enables us the in vitro diagnosis or primary carnitine deficiency.